Antibacterial Activities of Ephedra sinica Herb Extract on Standard and Clinical Strains of Pseudomonas aeruginosa - Bahman Fazeli-Nasab; Sayyede Razieh Mousavi (Journal of Medical Bacteriology, 2019)
Background:    Ephedra sinica Stapf (Ephedraceae) is one of the most important plants in traditional medicine and medicinally important as the botanical origin of crude drugs. The main active constituents of Ephedra sinica are the unique and taxonomically restricted adrenergic agonist’s phenylpropylamino alkaloids, also known as ephedrine alkaloids: norephedrine, norpseudoephedrine, ephedrine, pseudoephedrine, methylephedrine and methylpseudoephedrine.